Radiographic diagnosis of erosive hand osteoarthritis - D. M. Kudinsky; A. V. Smirnov; L. I. Alekseeva; A. V. Volkov; E. A. Taskina; А. M. Lila (Научно-практическая ревматология)
Osteoarthritis (OA) is one of the most common diseases of the musculoskeletal system in the world. Some researchers call the small joints of the hands as being one of the most common sites of involvement in OA. Its most severe phenotype is considered to be inflammatory, or erosive, OA (EOA). Nevertheless, the radiographic pattern of this disease has not yet been sufficiently studied, and whether EOA is an independent form of OA, a regular later stage of the disease or an individual nosological entity, has not yet been resolved.Objective: to assess the location, frequency, and severity of radiographic symptoms and pain in patients with EOA and non-erosive OA (NEOA), to study the involvement of carpometacarpal (CMC), wrist, metacarpophalangeal (MCP) and radiocarpal (RC) joints in the pathological process in patients with EOA and NEOA of the hands.Subjects and methods. The investigation enrolled 64 women with hand OA who met the American College of Rheumatology (ACR) OA criteria. Hand joint images in the anteroposterior projection were first performed in all the patients. Each patient completed the AUSCAN questionnaire. The images were described according to the Kellgren and Lawrence classification. The mean age of the patients was 65.28+6.82 years; the age at onset of the disease was 48.81+7.73 years; its median OA duration was 15.0 [10.0; 19.5] years. According to the presence of erosions in the interphalangeal joints (IPJ) of the hand, the patients were divided into two groups: 1) EOA (n=23); 2) NEOA (n=37). Both groups were matched for age and disease duration (the mean age of patients with EOA was 68+6.15 years, the mean disease duration was 18.34+7.11 years; these in the NEOA group were 65.13+5.43 and 16.56+8.4 years, respectively). For age matching, 4 patients were excluded from Group 2.Results and discussion. Kellgren and Lawrence Stage II hand OA was detected most frequently (49%) and the most common radiographic symptoms of OA in the distal IPJ (DIPJ), proximal IPJ (PIPJ) and MCP joints were joint space narrowing (JSN) (100%, 100%, and 95%, respectively) and osteophytes (OPs) (88%, 70%, and 45% respectively). The least common conditions were subchondral osteosclerosis (SCOS) (5%), erosions (8%), and subluxations (3%) in the MCP joints, as well as subluxations in the PIPJ (6%). In the wrist, the most frequent sites of involvement was first CMCJ and scaphoid-trapezium-trapezoid joint (STTJ); their JSN was identified in 86 and 69% of patients, respectively; OPs were found respectively in 81 and 50% of cases. Changes in the RC joint (RCJ) were least common.EOA of the DIPJ and PIPJ was found in 15 (23%) patients with radiographic changes corresponding to Stages III—IV OA of the hand and in 8 (12%) patients with Stage II according to the Kellgren and Lawrence classification. The DIPJ in EOA versus NEOA showed significantly higher frequency of OPs (100 and 78%), SCOS (74 and 11%), cysts (61 and 24%), and subluxations (43 and 14%); the PIPJ — SCOS (43 and 5%), cysts (52 and 27%), and subluxations (17 and 0%; p <0.05); the first CMCJ — JSN (96 and 68%), SCOS (61 and 22%), erosions (26 and 3%), and subluxations (39 and 14%), the STTJ, — SCOS (22 and 3%) and erosions (62 and 16%, respectively; p <0.05). According to the AUSCAN questionnaire, a significantly greater pain severity was recorded in patients with EOA than in those with NEOA (65 and 30%; p=0.008).Conclusion. DIPJs are most frequently affected by hand OA. The most common radiographic symptoms are JSN and OPs. In the wrists, first CMCJ and STTJ are most often involved; there are practically no changes in the RCJ. In EOA versus in NEOA, there are significantly more common OPs, cysts, SCOS, and subluxations in the DIPJs, SCOS, cysts, and subluxations in the PIPJs; first CMCJ and STTJ are significantly more often involved in the pathological process. EOA compared with NEOA is characterized by more severe pain, as evidenced by the AUSCAN questionnaire.